Oxford Essential Polish Dictionary Polish-English, English-Polish. (Oxford : Oxford University Press, 2010)
The 'Oxford Essential Polish Dictionary' is the ideal dictionary for easy and quick look-up in Polish or in English, including the latest contemporary vocabulary, and is great value for money.
Keywords: Polish language -- Dictionaries -- English; English language -- Dictionaries -- Polish; Languages